History, Religion, and Culture British Intellectual History 1750-1950 - Кононенко, В. (Інститут історії України НАН України, 2009)
Рецензія на книгу "History, Religion, and Culture British Intellectual History 1750-1950 / Edited by S. Collini. – Cambridge university press, 2000. – 289 Р."